6
$\begingroup$

Using Bezout's identity I have shown

$$(a,b^2)=(b,a^2)=1$$

but what should be the next step? Thanks.

$\endgroup$
  • 4
    $\begingroup$ HINT: for any prime $p$ , $p|\gcd(a^2,b^2)$, then $p^2|\gcd(a^2,b^2)$, thus we must have $p|\gcd(a,b)$. $\endgroup$ – asatzhh Aug 5 '13 at 12:47
7
$\begingroup$

Just to follow your idea with Bezout's.

$$ap+bq=1$$

implies (squaring and multiplying by $ap$) $$a^2ap^3+2p^2qa^2b+b^2apq^2=ap$$

and (similarly)

$$a^2bp^2q+2pq^2ab^2+b^2bq^3=bq$$

Adding them

$$1=a^2(bp^2q+ap^3+2p^2qb)+b^2(2pq^2a+bq^3+apq^2)$$

$\endgroup$
2
$\begingroup$

For any two integers $x,y$, $gcd(x,y)=1$ iff there exist $r,s\in \mathbb Z$ such that $rx+sy=1$.

So now, suppose $gcd(a,b)=1$ and write $ra+sb=1$. Square both sides and rearrange terms appropriately, and this proves that $gcd(a^2,b)=1$, and also that $gcd(a,b^2)=1$. This is presumably what you've done. So, for all $a,b\in \mathbb Z$, $gcd(a,b)=1$ implies $gcd(a^2,b)=gcd(a,b^2)=1$. Apply again and you get $gcd(a^2,b^2)=1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.